コトナル エンブン ニ タイスル ナンキョクサン ノトセニアカ ギョルイ Notothenia (Gobionotothen) gibberifronsトTrematomus newnesi ノ サイジョウ ヒソウ サイボウ ノ ケイタイ ヘンカ オヨビ イッパン ケイタイ ト コウドウジョウ ノ ヘンカ - Fanta, Edith; Luvizotto, Marcia Fabiana; Meyer, Ana Aparecida (1995)
P(論文) 南極沿岸の浅海域では, 海水の凍結, 融解に伴う塩分濃度の変化が顕著である。ここに生息する魚類が, いかに塩分の濃度の変化に適応しているかを調べるために, 南極半島, キングジョージ島, アドミラルティ湾産のNotothenia (Gobionotothen) gibberifronsとTrematomus newnesiを異なる塩分環境下で実験的に飼育した。鰓上皮層にある塩分細胞, 粘液分泌細胞の形態の変化を観察したところ顕著な変化が認められた。合わせて, 体色などの外部形態の変化, 行動の変化についての観察も行った。 In coastal Antarctic regions, melting and freezing affect water salinity. The aim of this study was to compare morphological changes of branchial epithelial cells in two species of Antarctic fishes, Notothenia (Gobionotothen) gibberifrons and Trematomus newnesi, and to detect behavioral consequences. They occur in Admiralty Bay (King George Island) during the summer, in a mean salinity of 32‰. Tests were conducted in the salinity range between 26‰ to 38‰ in experiments. Chloride cells in T. newnesi are roundish or elongated, with a small apex, at 32‰, thin with a large apex at low salinity, and roundish with small intrusions at the surface at 38‰. Chloride cells are elongated in N. (G.) gibberifrons at normal and low salinity, and increase in number, size and activity at 38‰ with large intrusions at the apical surface. In both species, mucous cells increase in volume, number and activity with salinity increase, being less active at low salinity. Epithelial detachment are observed at high salinity in T. newnesi and in low salinity in N. (G.) gibberifrons. Behavioral consequences of branchial cellular changes were observed : linear decrease of respiratory frequency with salinity increase; swimming decrease with salinity changes, except that at 26‰ forced swimming occurs and at 38‰ lethargy is interrupted by brisk jumps; paleness occurs with salinity decrease and darkness with salinity increase. These symptoms seem to be secondary consequences of hypoxia and ionic changes. departmental bulletin paper